Bullying dalam Perspektif Al-Qur’an: Analisis Nilai-Nilai Qur’ani sebagai Solusi Preventif dan Kuratif - Sholikhah, Novita Zaidatus; Makinuddin, Mohammad (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2025)
Bullying is a deviant behavior that frequently occurs in various social settings, particularly among students and adolescents. This behavior includes verbal, physical, and psychological abuse that can have long-term negative impacts on its victims. This study aims to examine the phenomenon of bullying and offer solutions based on the values contained in the Qur’an. The research adopts a qualitative method with a library research approach. Primary data sources include verses of the Qur’an related to the prohibition of harming others, the importance of noble character, and the exhortation to uphold justice and benevolence. Secondary data are obtained from classical and contemporary Qur’anic exegesis, literature on bullying, and relevant scholarly articles. The findings indicate that the Qur’an firmly condemns all forms of injustice and violence against fellow human beings. Moreover, it promotes values such as empathy, compassion, justice, and social responsibility as fundamental principles for both preventing and addressing bullying. Integrating Qur’anic values into character education is expected to foster the development of a healthier and more harmonious social environment